Is selling body parts ethical? / Christina Fisanick [editor] - Fisanick, Christina editor
Overview: Greenhaven Press's At Issue series provides a wide range of opinions on individual social issues. Each volume focuses on a specific issue and offers a variety of perspectives-eyewitness accounts, governmental views, scientific analysis, newspaper and magazine accounts, and many more-to illuminate the issue. Extensive bibliographies and annotated lists of relevant organizations point to sources for further research. Enhancing critical thinking skills, each At Issue volume is an excellent research tool to help readers understand current social issues and prepare reports.